1967
DOI: 10.2135/cropsci1967.0011183x000700040033x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Photoperiod on Metabolic Changes in Alfalfa in Relation to Cold Hardiness1

Abstract: Investigations were conducted to evaluate the effects of temperature and photoperiod on metabolic changes during development and maintenance of cold hardiness of two alfalfa (Medicago sativa L.) varieties varying widely in inherent cold hardiness. Cold temperatures appeared to be of primary importance for development and maintenance of cold hardiness, whereas both temperature and pbotoperiod played important roles in the metabolic processes.The content of protein, RNA, or DNA was positively associated with dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…This study seemed particularly appropriate because consistent increases in pH of plant sap have been observed during the acquisition of cold tolerance and the rises in pH were greater in cold-tolerant than cold-sensitive cultivars (6,7,11,12). Foliar applications of purines and pyrimidines that increased cold tolerance also tended to increase pH of plant sap (6).…”
Section: Discussionmentioning
confidence: 86%
“…This study seemed particularly appropriate because consistent increases in pH of plant sap have been observed during the acquisition of cold tolerance and the rises in pH were greater in cold-tolerant than cold-sensitive cultivars (6,7,11,12). Foliar applications of purines and pyrimidines that increased cold tolerance also tended to increase pH of plant sap (6).…”
Section: Discussionmentioning
confidence: 86%
“…(9) recently reported that an increase in RNA content precedes an increase in cold hardiiness of black locust. Two of our studies (3,8) provided evidence that RNA and DNA content of alfalfa plants were positively correlated wvith cold hardiness. Restults presented in table III appear to be only in partial agreement with the pre-vious findings.…”
mentioning
confidence: 69%
“…In addition to reduced height and weight growth in the fall, winterhardy cultivars have shorter and fewer internodes (Sheridan and McKee 1968) and a less erect growth habit (Larson and Smith 1963). Under certain conditions of temperature and photoperiod, winterhardy and nonwinterhardy cultivars show similar growth in height (Schonhorst et al 1951;Shih et al 1967 …”
mentioning
confidence: 99%